A study on the energy efficiency of specific cutting energy in laser-assisted machining. (5th February 2016) - Ahn, Jong Wook; Woo, Wan Sik; Lee, Choon Man
Highlights: Machining conditions were selected by thermal analysis of material. Specific cutting energy was compared for each depth of cut depending on the spindle rotation speed and feed rate. According to the specific cutting energy, the effectiveness of LAM is verified by comparing the conventional machining. Cutting force and specific cutting energy decreased at all depths of cut by the LAM in comparison to conventional method. Abstract: As hybrid machining approach, laser assisted machining (LAM) is a processing method used to improve productivity and surface quality, in which the workpiece is softened by laser preheating. LAM is also an effective method to save cutting energy by reducing cutting forces. In this study, the specific cutting energy was represented by tangential force and material removal rate (MRR). In order to analyze the thermal properties of the material, a thermal analysis was performed. The machining conditions were selected in accordance with the thermal analysis results. The specific cutting energy was compared for each depth of cut depending on the spindle rotation speed and feed rate. When compared to conventional processing in all conditions, LAM exhibited a higher efficiency in energy as well as the cutting force.